2014
DOI: 10.1515/folmed-2015-0002
|View full text |Cite
|
Sign up to set email alerts
|

Bone And Soft Tissue Changes In Patients With Spinal Cord Injury And Multiple Sclerosis

Abstract: In patients with spinal cord injury and multiple sclerosis, deterioration of body composition (changes in bone, fat and muscle mass) is associated with increased risk for diseases such as coronary artery heart disease, non-insulin dependent diabetes mellitus, lipid metabolism abnormalities, and osteoporotic fractures in these patients. Immobility leads to a changing pattern of loading in the paralyzed areas, and secondary alteration in structure. However, bone and soft tissue changes in these patients are usua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…These patients are different from the patients in bed rest studies, and require rehabilitation that is not highly intensive and is able to target specific muscle and bone groups. 65 Dauty et al 66 found that the loss of bone mass is greatest in the lower limb (70% in the distal femur and 52% in the proximal tibia) in spinal cord injury patients. Such patients with paralysis would have to rely on vibration technology which simulates neuromuscular activation and induces mechanical stress on bone.…”
Section: Discussionmentioning
confidence: 99%
“…These patients are different from the patients in bed rest studies, and require rehabilitation that is not highly intensive and is able to target specific muscle and bone groups. 65 Dauty et al 66 found that the loss of bone mass is greatest in the lower limb (70% in the distal femur and 52% in the proximal tibia) in spinal cord injury patients. Such patients with paralysis would have to rely on vibration technology which simulates neuromuscular activation and induces mechanical stress on bone.…”
Section: Discussionmentioning
confidence: 99%
“…A paraplegic subject could be wheelchair bound, may have an alternated walking gait pattern but may also be unable to walk at all [10,11]. In addition to these differences and according to osteoporosis the role of factors which do not change, such as race or gender of patients has not been yet clarified, although there are few studies in women debating that bone mass in women with paraplegia is more affected than men [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The acute SCI could result in a bruise, a partial tear, or a complete tear in the spinal cord (Alkabie & Boileau, 2015;Sothmann et al, 2015). The primary SCI could degrade key cytoskeletal and activate functional proteins, leading to delayed death of local and adjacent neurons and glial cells (Dionyssiotis et al, 2014;Henke et al, 2015). Primary injury is considered to be an irreversible mechanical damage (Evaniew et al, 2015).…”
Section: Introductionmentioning
confidence: 99%